LEVEL ACCOUNTING DAN HISTORICAL COST ACCOUNTING DALAM MENGUKUR PROBABILITAS FINANCIAL DISTRESS - B2091141004, JANNI WIRYANI (MAKSI UNTAN, 2016)
This study intends to examine and explain the differences between financialreport based on the general price level accounting and financial report based on historical cost accounting and the differences in measuring the probability of financial distress. This study uses secondary data from the financial report of banks liesting in Indonesia Stock Exchange 2011-2015. Analytical tools used are some of the ratios contained in CAMEL ratios, Altman Z score and the average difference test. Based on the results of the study it can be concluded that there is a difference between the historical cost accounting with the general price level accounting. if the inflation rate is high, the financial statements are prepared based on the historical cost andÂ  financial statements prepared based on general price level accounting will have a higher difference too. The results also showed that there are significant differences between general price level accounting with historical cost accounting to measure the probability of financial distress. Keywords: Historical Cost Accounting, General Price LevelÂ  Accounting, and Financial Distress